Patellar resurfacing versus nonresurfacing in total knee arthroplasty: an updated meta-analysis of randomized controlled trials - Kai Chen; Xiaoyu Dai; Lidong Li; Zhigang Chen; Haidong Cui; Shujun Lv (2021)
Abstract Background Whether resurface the patella or not in total knee arthroplasty (TKA) was controversial. In 2013, we conducted a meta-analysis of randomized controlled trials (RTCs). After that, plenty of studies have been carried out, but there still existed a great deal of controversy. In order to update our previous study, we conducted this update meta-analysis to evaluate the efficacy of patellar resurfacing in TKA. Methods Databases were searched for RCTs comparing the outcomes of patellar resurfacing and nonresurfacing in TKA. Outcomes of knee relevant indicators were analysed. To see the short- and long-term effects, we calculated the data in total and divided the patients who were followed up for ≤ 3 years and ≥ 5 years into two subgroups as well. Results Thirty-two trials assessing 6887 knees were eligible. There was a significant difference in terms of reoperation (in total and ≥ 5 years), Knee Society Score (KSS), function score (in total and ≥ 5 years) and noise. While no significant difference was found in the following items: reoperation (≤ 3 years), anterior knee pain (AKP), function score (≤ 3 years), range of motion (ROM), Oxford score, the Knee Injury and Osteoarthritis Outcome Score (KOOS), visual analogue score (VAS), Feller score, patellar tilt and the patients’ satisfaction. Conclusions We found that patellar resurfacing could reduce the occurrence of reoperation and noise after surgery, as well as increase the KSS and function score, while it might not influence the outcomes such as AKP, ROM, Oxford score, KOOS, VAS, Feller score, patellar tilt and the patients’ satisfaction. The results are different from our previous finding in the meta-analysis. In conclusion, we prefer patellar resurfacing in TKA.